Appraisement of Mental Health Manifestations among Hypertensive Patients - Salah Hassan Yousif (Zanco Journal of Medical Sciences, 2023)
Background and objective: Hypertension is a growing public health problem worldwide; hypertensive patients experience negative emotions, which in particular may increase the risk for mental health instabilities. The objective of the study was to find out the prevalence of anxiety and depression among hypertensive patients.